Language choice in online written communication among Maldivian professionals - Fathimath Fahmee,; Yong, Mei Fung (Penerbit Universiti Kebangsaan Malaysia, 2016)
Language choice is a sociolinguistic phenomenon which refers to the selection of language(s) for different purposes in various contexts. This study examines the language choice of Maldivians in online written communication in the domains of family, friendship and work. Dhivehi is the unique Indo-Aryan language spoken almost exclusively in the Maldives along with English as the unofficial second language. A total of 150 professionals from the fields of education, administration and health took part in the study with academic qualifications ranging from diploma to doctorate degree. The data was collected using a survey questionnaire and analysed quantitatively. The findings revealed that Dhivehi is the dominant language in the family domain while English is dominant in the friendship and work domains. There is also a relationship between language choice and age, and English language proficiency. The high preference for English in online written communication indicates a need for a language policy that would emphasise and increase the use of Dhivehi online as a language maintenance effort.